Dynamic modelling of semitrailer trucks equipped by steered wheels - Diachuk, M.; Lykhodii, O.; Leontiev, D.; Ryzhykh, L.; Aleksandrov, Yu. V.; Александров, Ю. В. (Journal of Mechanical Engineering and Sciences. – 2022. – Vol. 16, Issue 1. – P. 8691–8705, 2022)
Improving the performance of articulated vehicles is not only by completing the tractor systems, but also by intellectualizing the trailer links (TL), is a complex task. In this regard, the search for and justification of the implementation of controlled TL systems is an important process (Intelligent Trailer). The research has been carried for the purpose of development of the systemic approach from the idea schematization to the practical recommendations. The paper proposes a general approach for creating a comprehensive calculation model that establishes a link between the dynamics of movement of articulated vehicle and the active controlling systems of the semitrailer. The key moments is the developed mathematical model based on matrix technique that facilitates the creation of the universal simulation model in the Simulink environment. The created method with recommended programming product afforded to increase the exactness of modelling of curving way of articulated vehicle on 10 % under the diminishing of time on the calculation about 50 % in comparison with classical method. At the expense of experimental investigation there was confirmed appropriateness of proposed imitation model of movement dynamics of articulated vehicle, general relative mistake in comparison with theoretical investigations was not over than 5%. Additional combining to semitrailer chassis the active turning control system diminishes the size line of constant movement of articulated vehicle in the circle on 14,5% in comparison with semitrailer without this system, which is also positive from the point of safety of articulated vehicle maneuverability.

Улучшение эксплуатационных характеристик сочлененных транспортных средств не только за счет доработки систем тягача, но и за счет интеллектуализации прицепных звеньев (ПЗ), является сложной задачей. В связи с этим поиск и обоснование внедрения управляемых систем ПЗ является важным процессом (Intelligent Trailer).

Поліпшення експлуатаційних характеристик зчленованих транспортних засобів не лише за рахунок доопрацювання систем тягача, а й за рахунок інтелектуалізації причіпних ланок (ПЗ) є складним завданням. У зв'язку з цим пошук та обґрунтування впровадження керованих систем ПЗ є важливим процесом (Intelligent Trailer).
Keywords: publikatsii u WoS; Техніка. Технічні науки. Machinery. Engineering. Техника. Технические науки; steer-by-wire; trailer's steered wheels; simulink-model; vehicle dynamics; semitrailer trucks; steering system; электронное управление; рулевое управление прицепа; модель Simulink; динамика транспортного средства; полуприцепы; система рулевого управления; рульове управління; рульові колеса причепа; simulink-модель; динаміка автомобіля; вантажівки з напівпричепами; система рульового управління